12TH KEY SYMPOSIUM – Insulin resistance in common diseases. (November 2016) - Unknown
Abstract : JIM Podcast – JIM Editor, Bo Angelin, interviews Ulf Smith about the 12th Key Symposium at Harvard on Insulin resistance in common diseases. Ulf Smith brings up important aspects and future perspectives of the research in this broad field.